Nasal inflammation and its response to local glucocorticoid regular treatment in patients with persistent non-allergic rhinitis: a pilot study - Poletti, Donatella; Iannini, Valeria; Casolari, Paolo; Contoli, Marco; Papi, Alberto; Kirkham, Paul; Hansel, Trevor T.; Chung, Kian Fan; Barnes, Peter J.; Pastore, Antonio; Pelucchi, Stefano; Adcock, Ian M.; et al. (Journal of inflammation (London, England), 2016)
The pathogenesis of non-allergic rhinitis (NAR) is still largely unknown. Furthermore, it is unclear whether there is a correlation between the effect of nasal glucocorticoids on nasal inflammation and on nasal symptoms and quality of life. In this pilot study we recruited 12 healthy subjects and 24 patients with recently diagnosed persistent NAR [12 untreated and 12 under regular treatment with nasal fluticasone furoate (two sprays of 27.5 μg each in each nostril once daily, total daily dose = 110 μg) for at least 20 days]. Each subject filled a mini rhinoconjunctivitis quality of life questionnaire (mini RQLQ). Nasal scrapings were obtained from each subject and used to prepare slides for Diff-Quik and immunocytochemical staining for inflammatory and epithelial cells count, MUC5AC expression and the general pro-inflammatory transcription factor nuclear factor kB (NF-kB) activation. The nasal score of the mini RQLQ, the number of nasal inflammatory cells (neutrophils, eosinophils) and the number of goblet cells are significantly higher in untreated patients with persistent NAR compared with control subjects and treated NAR patients. The percentage of MUC5AC+ nasal epithelial cells is significantly increased in untreated patients with persistent NAR compared with the control subjects (41.8 ± 6.4 vs 22.3 ± 4.8, respectively; p = 0.0403) without significant differences between control subjects and patients with persistent NAR on regular fluticasone furoate treatment (33.9 ± 5.0 %; p = 0.0604) nor between the 2 groups of persistent NAR subjects (p = 0.3260). The number of cytosolic and/or nuclear p65+ nasal epithelial and inflammatory cells was not significantly different between the three groups. Patients with persistent untreated NAR, compared with normal control subjects and patients with persistent NAR under regular treatment with nasal fluticasone furoate by at least 20 days, have more nasal symptoms, worst quality of life and an increased number of nasal inflammatory cells (neutrophils, eosinophils), goblet cells and MUC5AC+ nasal epithelial cells. This nasal inflammation seems unrelated to NF-kB activation.